Pengaruh Bahan Pengikat terhadap Sifat Kimia dan Organoleptik Produk Nugget Tempe - Hartati; A. Faridah Arsal; Rachmawaty (Bionature, 2009)
The diversification limitation of exploiting tempe as an alternative nugget raw materials, substitution of meat and fish, and also to optimalize the very abundance resource, so it is necessary to do the right processing to the alternative food resource, which meant to give an additional point. Produce a liked product, also the adjustment of technology, and the cost that reached by the society. The aim of this reseach is to know the kind of glue material which can produce nugget tempe with the best chemical and organoleptic propertics. This research consit of 4 treatment; A1 (tempe nugget from bread powder), A2 (tempe nugget from tapioca), A3 (tempe nugget from sagu), A4 (tempe nugget maizena powder). Water convcentration analyse using oven method. Product was tested by organoleptic test (taste, smell, and tecsture). The result on water concentration analyse, that the smallest water concentration shown by A2 about 161,55% between from treatment A1 abaout 191,75%, A3 abaout 180,02% and A4 182, 45%. The result on organoleptic the teste of A1 product is the most like (75 %) between A2, A3 and A4 treatment. The smell of A2, A3 and A4 is the must like (67 %). And the best tecsture is all treatment.The result of this research is expected to give benefit in supporting the effort saking the alternative nugget glue material by using tempe which owning a high nutrition value. This research it is expected to find a kind if nugget tempe with the good glue, good taste and high nutrition value.